PENGARUH PENATALAKSANAAN TERAPI LATIHAN TERHADAP KEPUASAN PASIEN FRAKTUR DI IRINA A BLU RSUP PROF. DR. R.D. KANDOU MANADO - Hendrik H. Damping (POLTEKKES KEMENKES MANADO, 2012)
Rehabilitation treatment in patients with fractures include physical therapy, which consists of varioustypes of exercises: isometric muscle exercises and active and passive ROM exercises. Exercise therapy isone treatment efforts in the implementation of physiotherapy exercises using body movements, eitheractively or passively (Kisner, 1996). The goal of rehabilitation exercise therapy is to address the functionand movement disorders, prevent complications, reduce pain and edema as well as functional activity dueto train operations. This study uses a pre-experiment design with the research method that is static groupcomparison, sample of 49 people consisting of 24 people sampled in the experimental group and 25samples in the control group. data processing is done through analysis of test Chi Square (X ²) of twosamples. The results of patient satisfaction rate of fracture after receiving the treatment (experimentalgroup) were 22 respondents were satisfied and 2 respondents were not satisfied to exercise therapy given.While the group did not receive treatment that is there are 24 people were not satisfied and only oneperson who was satisfied, chi square analysis of two samples based on the results of each group thenfound count rates χ2 χ2 is greater than the price of a good table for the standard error of 5% or 1%. Thereare differences in satisfaction levels between the two groups of fracture patients to exercise therapy.There is the influence of exercise therapy for treatment of fractures of patient satisfaction in thedepartment of Prof. Irina A BLU. Dr. R.D. Kandou Manado.